2022
DOI: 10.1186/s12884-022-04729-5
|View full text |Cite
|
Sign up to set email alerts
|

Implementing “Online Communities” for pregnant women in times of COVID-19 for the promotion of maternal well-being and mother-to-infant bonding: a pretest–posttest study

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic elevated the risk for mental health problems in pregnant women, thereby increasing the risk for long-term negative consequences for mother and child well-being. There was an immediate need for easily accessible interventions for pregnant women experiencing elevated levels of pandemic related stress. Methods A three-session intervention “Online Communities” (OC) was developed at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…As researchers expect that not only will COVID-19 continue to evolve and spread but that there are a number of other viruses that may lead to pandemics or endemics ( Behl et al, 2022 ; Telenti et al, 2021 ), providers, policy makers, and researchers should consider how to improve mental health for obstetric patients during health crises. This can be accomplished by implementing regular screening practices, coordinating care and referrals for individuals with high levels of symptoms, promoting online interventions, or increasing virtual social support ( Potharst et al, 2022 ; Puertas-Gonzalez et al, 2021 ; Suwalska et al, 2021 ). Incorporating these strategies pre-emptively may prevent negative maternal and fetal outcomes in future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…As researchers expect that not only will COVID-19 continue to evolve and spread but that there are a number of other viruses that may lead to pandemics or endemics ( Behl et al, 2022 ; Telenti et al, 2021 ), providers, policy makers, and researchers should consider how to improve mental health for obstetric patients during health crises. This can be accomplished by implementing regular screening practices, coordinating care and referrals for individuals with high levels of symptoms, promoting online interventions, or increasing virtual social support ( Potharst et al, 2022 ; Puertas-Gonzalez et al, 2021 ; Suwalska et al, 2021 ). Incorporating these strategies pre-emptively may prevent negative maternal and fetal outcomes in future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, access to the internet and proficiency in computer skills were associated with a higher purchasing power and educational level. A previous study found that younger participants using an online recruitment method were more prone to drop out of the study than older and more educated participants [ 21 , 23 , 36 ]. According to these studies, older pregnant mothers with a high educational level are more likely to use the Internet to seek information regarding their health and participate in online evaluation and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the traditional resources and strategies to monitor pregnancy and prepare women for birth were blocked or delayed in an attempt to constrain the ever-expanding SARS_CoV-2 and to provide spaces to respond to the COVID-19 pandemic. New approaches were introduced, substituting antenatal face-to-face appointments with phone calls, video chats and other online approaches [ 17 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations